One Step Anti-Windup Based State Feedback Controller Design for Constrained T-S Systems - Ju, Kaizhong; He, Hanlin; Zha, Miao (Chinese Control Conference, 2018)
This paper proposes an LMI-based method to guarantee the closed-loop regional stability for the state feedback control of Takagi - Sugeno systems that are subject to input saturation and state constraints. Based on the Lyapunov stability analysis, a bi-linear stabilization criterion is proposed, which can be changed into LMI criterion based on congruent transformation. The proposed method provides conditions to simultaneously design the state feedback controller and its anti-windup compensator. The effectiveness of the proposed method is illustrated with the chaotic Lurie system control.